Resting and action potentials under hypotonic conditions, unlike Na+ pump activity, depend only on the alteration of intracellular [Na+] and [K+] in frog skeletal muscle - Venosa, Roque (2011)
It is well established that hypotonicity generates a marked and unexpected increase in active Na+ efflux in frog muscle fibers as well as in other cells like cardiac myocytes, astrocytes, brain synaptosomes and renal cells. The effect of hypotonicity on the electrical activity of skeletal muscle related to Na+ and K+ voltage-gated channels, however, has not been specifically addressed. The results of the present investigation show that the changes in resting and action potentials produced by hypotonicity can be fully explained by the reduction of intracellular [Na+] and [K+] due to the increase in cellular water content.